Clinical significance of ferroptosis as iron-dependent regulated cell death in the general structure of the disease - H.O. Lezhenko; A.E. Abaturov; A.O. Pogribna (Zaslavsky O.Yu., 2022)
In this article, we have analysed the studies that determined the iron-dependent regulated type of cell death, ferroptosis, described the fundamental morphological and biochemical differences between various types of regulated cell death, highlighted modern scientific achievements in understanding the features of the above-mentioned process, described the clinical significance of ferroptosis in the general structure of morbidity and identified relevant issues for further research. Conclusions. Numerous studies allowed identifying ferroptosis as a form of regulated cell death, initiated by oxidative disturbances of the intracellular microenvironment, which is under the constitutive control of glutathione peroxidase 4 and can be inhibited by iron chelators and lipophilic antioxidants. Ferroptosis can occur in two main ways: external (transport) and internal (enzymatic). The external pathway is based on non-enzymatic reactions, such as the iron-dependent Fenton reaction. The internal pathway is mediated by enzyme systems, including glutathione peroxidase 4 and lipoxygenase. Conducting clinical research will improve not only the understanding of the role of ferroptosis in the pathogenesis of the course of diseases, but also reveal possible preventive strategies for the development of pathological processes.